Of sex, families, and psychology: A sibling-comparison analysis of the influence of adverse psychological effects on sexual and familial behaviors - Nedelec, Joseph L; Silver, Ian A; Province, Karli; Theocharidou, Kalliopi (Personality and individual differences, 2021)
AbstractA central focus of lifecourse and developmental research centers on the ways in which individual differences impact a wide swath of behavioral outcomes. While the bulk of this research has informed our understanding of how individual personality traits may influence life outcomes, relatively less attention has been paid to how the co-occurrence of multiple aspects of psychological symptomologies can affect variation in behaviors across the life course. Furthermore, broad segments of prior literature on the influence of psychological symptomologies on behavioral outcomes are subject to genetic confounding. The current study thus employed a latent measure of a single overarching psychological system tapping the co-occurrence of negative psychological symptoms – termed adverse psychological effects – within a genetically-informed methodology. Longitudinal analyses of twin dyads drawn from the National Longitudinal Study of Adolescent to Adult Health ( n = 1370 [ nMZ = 530; nDZ = 840]) revealed a variety of between-family effects of adverse psychological symptomologies on sexual and familial behaviors. Most of the within-family effects, however, were null. The results illustrate the importance of accounting for shared genetic and non-genetic factors in assessments of the effects of individual differences on life outcomes within the social sciences.